T.JUMAMURATOV SHÍǴARMALARÍNDA KÓMEKSHI SÓZLERDIŃ STILLIK QOLLANÍLÍWÍ - Bekniyazov, Q.I.; Shınnazarov, N.J. (SCIENCE and SOCIETY, 2021)
The article is devoted to the work of T.Jumamuratov, his linguistic side. The methodological use of auxiliary words is mainly analyzed. Questions related to the stylistic use of auxiliary words and through the poet's poems.
Keywords: conjuction; particle; auxiliary words; language style; language of literary work; lexeme